2012
DOI: 10.1016/j.molcel.2012.04.026
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Mammalian Caspases as Positive and Negative Regulators of Inflammation

Abstract: Members of the caspase family of cysteine proteases coordinate the morphological and biochemical events that typify apoptosis. However, neutralization of caspase activity in mammals fails to block death in response to most proapoptotic stimuli. This is because many cell death triggers provoke mitochondrial dysfunction upstream of caspase activation as a consequence of BAX/BAK channel opening. Although genetic or pharmacological inactivation of caspases fails to block cell death in most instances, it does conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(158 citation statements)
references
References 62 publications
1
154
0
3
Order By: Relevance
“…In the absence of being phagocytosed, apoptotic cells undergo secondary necrosis and lyse; however, even in this situation they might fail to stimulate an inflammatory response. This has led to the proposal that rather than being required for cell death, caspases serve to inactivate DAMPs (Martin et al, 2012). Various data support this idea, in that caspases -either by direct cleavage or indirectly -have been shown to inactivate various DAMPs, including HMGB1 and IL-33 (Kazama et al, 2008;Lüthi et al, 2009).…”
Section: Does It Matter How a Cell Dies?mentioning
confidence: 99%
“…In the absence of being phagocytosed, apoptotic cells undergo secondary necrosis and lyse; however, even in this situation they might fail to stimulate an inflammatory response. This has led to the proposal that rather than being required for cell death, caspases serve to inactivate DAMPs (Martin et al, 2012). Various data support this idea, in that caspases -either by direct cleavage or indirectly -have been shown to inactivate various DAMPs, including HMGB1 and IL-33 (Kazama et al, 2008;Lüthi et al, 2009).…”
Section: Does It Matter How a Cell Dies?mentioning
confidence: 99%
“…A landmark study has implicated necrotic cells are sensed by the NLRP3 inflammasome resulting in the subsequent pro-inflammatory cytokine IL-1ß release ( Figure 10) [100]. Early examples of research reported that caspases served to inactivate DAMPs ( [101][102][103], thereby caspases could be viewed as cell death effectors and regulators of inflammation [103].…”
Section: Necrosismentioning
confidence: 99%
“…Caspase-9 undergoes auto-processing and then cleaves the effector caspase-3 and caspase-7, resulting in their activation. Caspase-3 (and caspase-7) activity mediates all the hallmarks of apoptosis, such as nuclear condensation, oligonucleosomal DNA cleavage, phosphatidylserine exposure and the shut-off of respiration, resulting in cell death and immediate uptake of apoptotic cells by phagocytes, in general without triggering inflammation (Martin et al, 2012;Riedl and Salvesen, 2007) .…”
Section: Box 2 Intrinsic and Extrinsic Apoptosis Pathwaysmentioning
confidence: 99%